Prescripción de antibióticos en niños de 0 a 10 años afiliados al seguro integral de salud atendidos en el centro de salud Liberación Social, Setiembre 2014 - febrero 2015 - Pereda Villajulca, Zúsel Bettina (2015)
The main objective of this study is to determine the prescription of antibiotics in patients 0-10 years affiliates to Integral Health Insurance (SIS) treated at the Health Center for Social Liberation (September 2014-February 2015). The study follows the simple, descriptive retrospective cross design. 483 recipes were evaluated patients affiliated to the SIS between the months of September 2014 through February-2015, which represented 74% of children aged 0 to 5 years and 26% for 6 to 10 years; as to the group of antibiotics identified within the single National Petition of Essential Medicines (Pnume) is 69% for penicillin, sulfonamides followed with 17% and miscellaneous and macrolides with 7 and 6% respectively; Antimicrobial regarding its International Nonproprietary Name (INN), amoxicillin is the most prescribed 64%, the trimethoprim / sulfamethoxazole with 17% and 6% dicloxacillin; concerning the antibiotic prescribed by the age group of 0-5 years were most prescribed antibiotics benzylpenicillin benzathine (100%), erythromycin (91%), furazolidone (86%), trimethoprim / sulfamethoxazole (79%), azithromycin (75 %) and amoxicillin (72%), while for children 6 to 10 years gentamicin (50%), metronidazole (43%), dicloxacillin (33%), amoxicillin (28%), azithromycin (25%) and finally the trimethoprim / sulfamethoxazole (21%); finally during the semester September 2014-February 2015, amoxicillin and erythromycin had higher prescription in December (21% and 35%), dicloxacillin, azithromycin and metronidazole in January with 26%, 75% and 43% respectively, furazolidone more prescription in November (38%), and finally gentamicin and trimethoprim / sulfamethoxazole, reached 50% and 24% respectively in October. It is concluded that antibiotics have a high prescription in pediatric patients, these being unnecessary for some diagnostics, which involves the growth of bacterial resistance in this group of patients